Tom Jones As a Picaresque Novel: Exploring Tom Jones as a Significant Picaresque Novel in English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The History of Tom Jones a founding often known simply asTom Jones is a comic novel by the English playwright and novelist Henryfielding. The novel is both a bildungsroman and picaresque novel. It was firstpublished on February 1749, Tom Jones is among the earliest English prose worksdescribable as a novel and is the earliest novel mentioned by W. SomersetMaugham in his 1948 book ‘Great novelist and their novels” among the ten bestnovels of the world Totaling 3461747 words, it is divided into 18 smallerbooks, each preceded by a discursive to the book itself.